Case Report: Early Transplant Rejection of a Methanol-Intoxicated Donor Heart in a Young Female Patient. A Diagnostic Approach With CMR, Cardiac Biopsy, and Genetic Risk Assessment - Stoiber, Lukas; Schoenrath, Felix; Knosalla, Christoph; Milting, Hendrik; Klingel, Karin; Tschöpe, Carsten; Tanacli, Radu; Gebker, Rolf; Berger, Alexander; Pieske, Burkert; Kelle, Sebastian (Frontiers in Immunology, 2021)
This case report describes the contributions of multimodality imaging, cardiac biopsy, and gene sequencing to the diagnosis and management of heart transplant rejection in a 23-year old patient with dilated cardiomyopathy.